Adipokine Retinol Binding Protein 4 and Cardiovascular Diseases - Ji, Yanjing; Song, Jinyou; Su, Tianhong; Gu, Xiaosong (Frontiers in Physiology, 2022)
Abstract: The morbidity and mortality of cardiovascular diseases (CVD) has been increasing year by year all over the world and expanding greatly to the younger population, which becomes the leading causes of death globally that threatens human life safety. Prediction of the occurrence of diseases by using risk related adverse events is crucial for screening and early detection of CVD. Thus, the discovery of new biomarkers that related to risks of CVDs are of urgent in the field. Retinol-binding protein 4 (RBP4) is a 21-kDa adipokine, mainly secreted by adipocytes. Besides its well-established function in the induction of insulin resistance, it has also been found in recent years to be closely associated with CVDs and other risk factors, such as hypertension, coronary heart disease, heart failure, obesity, and hyperlipidemia. In this review, we mainly focus on the progress of research that establishes the correlation between RBP4 and CVDs and the corresponding major risk factors in recent years.